Optimising clinical performance during resuscitation using video evaluation. Issue 1102 (16th December 2016) - Lowe, David J; Dewar, Alistair; Lloyd, Adam; Edgar, Simon; Clegg, Gareth R
ABSTRACT: Video evaluation of resuscitation is becoming increasingly integrated into practice in a number of clinical settings. The purpose of this review article is to examine how video may enhance clinical care during resuscitation. As healthcare and available therapeutic interventions evolve, re-evaluation of accepted paradigms requires data to describe current practice and support change. Analysis of video recordings affords creation of a framework to evaluate individual and team performance and develop unique and tailored strategies to optimise care delivery. While video has been used in a number of non-clinical settings, there has been a recent increase of video systems in the prehospital and other clinical areas. This paper reviews the key opportunities in the emergency department-based resuscitation setting to enhance ergonomics, technical and non-technical skills—at both team and individual level—through video-assisted care performance analysis and feedback.